Importance of genetic testing in global health during the evaluation of familial microcephaly. Issue 10 (26th August 2016) - Molinero, Isaac; Broman‐Fulks, Jordan; Lyons, Michael J.; Matheus, Maria Gisele; Chaubey, Alka; DuPont, Barbara R.; Friez, Michael J.; Skinner, Steve A.; Holden, Kenton R.
Key Clinical Message: A focused genetic workup is useful in determining the cause of familial microcephaly, especially in the setting of mildly different phenotypes. As illustrated by this case from an impoverished international urban location, one must not assume the etiology for the apparent familial microcephaly is the same for all affected members. Abstract : A focused genetic workup is useful in determining the cause of familial microcephaly, especially in the setting of mildly different phenotypes. As illustrated by this case from an impoverished international urban location, one must not assume the etiology for the apparent familial microcephaly is the same for all affected members.